2016
DOI: 10.1016/j.heares.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of inferior colliculus activity to the auditory brainstem response (ABR) in mice

Abstract: In mice, the auditory brainstem response (ABR) is frequently used to assess hearing status in transgenic hearing models. The diagnostic value of the ABR depends on knowledge about the anatomical sources of its characteristic waves. Here, we studied the contribution of the inferior colliculus (IC) to the click-evoked scalp ABR in mice. We demonstrate a non-invasive correlate of the IC response that can be measured in the scalp ABR as a slow positive wave P with peak latency 7-8 ms when recorded with adequate ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 56 publications
3
37
0
Order By: Relevance
“…Besides the expected latency differences of about 1 ms between the wave peaks (Table 1), which relate to synaptic levels in the ascending auditory pathway [28,29,32,34], we found an average latency difference of 0.342 ms related to P1 when generated by high (50 kHz) vs. low (3.8 kHz) tone stimulation (Table 1, Δ D - A ). The frequency of 3.8 kHz is at the low end, 50 kHz at the high end of characteristic frequencies of AN fibers and IC neurons in NMRI mice [67,68] and other mouse strains [6971].…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Besides the expected latency differences of about 1 ms between the wave peaks (Table 1), which relate to synaptic levels in the ascending auditory pathway [28,29,32,34], we found an average latency difference of 0.342 ms related to P1 when generated by high (50 kHz) vs. low (3.8 kHz) tone stimulation (Table 1, Δ D - A ). The frequency of 3.8 kHz is at the low end, 50 kHz at the high end of characteristic frequencies of AN fibers and IC neurons in NMRI mice [67,68] and other mouse strains [6971].…”
Section: Discussionsupporting
confidence: 50%
“…The perceptual boundary near 100 ms depending on the duration of inter-sound intervals [15,16] was reflected in the beginning of significant adaptation of latencies and the increase of latency jitter at P5 for ISIs < ~100 ms (experiment C, Figs 5A, 6A and 6C). Thus, we can state that optimal perception of wriggling call series in one acoustic stream with ISIs > 100 ms happens when the sound onset responses at P5, most probably representing IC-responses in the mouse [3234], are largely free from adaptation and able to follow with full temporal precision the sound onsets. Likewise in human perception, series of two tones with frequencies within one critical band are integrated in one perceptual stream, if the ISIs are longer than about 100 ms [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present investigation, we focused on protein composition in the inferior colliculi rather than the auditory cortex, because the inferior colliculus actively contributes to the generation of the evoked ABRs (Land et al, 2016 ). We reasoned that the functional changes seen in ABR profiles might be linked to changes occurring in AMPA, Arc, Syt1, Syt12, at the protein level, as those are involved in the synaptogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In a first proof‐of‐principle study (Hernandez et al , ), optogenetic activation of the auditory system was reported in transgenic mice broadly expressing ChR2 in neural structures under the Thy1.2 promoter (Arenkiel et al , ). The feasibility of optogenetic excitation of the auditory system was first demonstrated by recordings of auditory brainstem responses (ABR): ABRs are far‐field potentials, reflecting the synchronous activation of the auditory system up to the auditory midbrain and are typically characterized by five waves (originating from activation of the auditory nerve, a set of nuclei in the auditory brainstem and finally the inferior colliculus (Henry, ; Land et al , )) when elicited by acoustic stimulation (aABRs). Using optogenetic (oABR) stimulation, it could be demonstrated that cochlear optogenetics is capable of evoking potentials of up to 2.5 mV amplitude.…”
Section: A Primer To Acoustic Electric and Optogenetic Hearingmentioning
confidence: 99%